ATP11B mediates platinum resistance in ovarian cancer - Moreno-Smith, Myrthala (American Society for Clinical Investigation, 2013)
Platinum compounds display clinical activity against a wide variety of solid tumors; however, resistance to these agents is a major limitation in cancer therapy. Reduced platinum uptake and increased platinum export are examples of resistance mechanisms that limit the extent of DNA damage. Here, we report the discovery and characterization of the role of ATP11B, a P-type ATPase membrane protein, in cisplatin resistance. We found that ATP11B expression was correlated with higher tumor grade in human ovarian cancer samples and with cisplatin resistance in human ovarian cancer cell lines. ATP11B gene silencing restored the sensitivity of ovarian cancer cell lines to cisplatin in vitro. Combined therapy of cisplatin and ATP11B-targeted siRNA significantly decreased cancer growth in mice bearing ovarian tumors derived from cisplatin-sensitive and -resistant cells. In vitro mechanistic studies on cellular platinum content and cisplatin efflux kinetics indicated that ATP11B enhances the export of cisplatin from cells. The colocalization of ATP11B with fluorescent cisplatin and with vesicular trafficking proteins, such as syntaxin-6 (STX6) and vesicular-associated membrane protein 4 (VAMP4), strongly suggests that ATP11B contributes to secretory vesicular transport of cisplatin from Golgi to plasma membrane. In conclusion, inhibition of ATP11B expression could serve as a therapeutic strategy to overcome cisplatin resistance.